2005
DOI: 10.1158/0008-5472.can-05-0724
|View full text |Cite
|
Sign up to set email alerts
|

8-Oxoguanine Formation Induced by Chronic UVB Exposure Makes Ogg1 Knockout Mice Susceptible to Skin Carcinogenesis

Abstract: 8-Oxoguanine is one of the oxidative DNA damages that can result in stable mutations. The Ogg1 gene encodes the repair enzyme 8-oxoguanine-DNA glycosylase, which removes the oxidized base from DNA. In this study, we investigated the role of 8-oxoguanine in skin carcinogenesis induced by UVB irradiation using Ogg1 knockout mice (C57Bl/6J background). We examined the effect of UVB irradiation on the formation of 8-oxoguanine in epidermal cells using immunostaining and found that the level of 8-oxoguanine in Ogg1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 15 publications
4
95
0
1
Order By: Relevance
“…The inactivation or knockdown of mouse OGG1 gene also led to the accumulation of 8-oxoG, followed by an increase in the mutation frequency in liver, kidney, and skin (47,48). Thus, we investigated the genomic profile of hOGG1-depleted cells in chronic exposure of H 2 O 2 to detect the gains or the losses of specific oncogenes and tumorsuppressor genes.…”
Section: Discussionmentioning
confidence: 99%
“…The inactivation or knockdown of mouse OGG1 gene also led to the accumulation of 8-oxoG, followed by an increase in the mutation frequency in liver, kidney, and skin (47,48). Thus, we investigated the genomic profile of hOGG1-depleted cells in chronic exposure of H 2 O 2 to detect the gains or the losses of specific oncogenes and tumorsuppressor genes.…”
Section: Discussionmentioning
confidence: 99%
“…29 These lamps emit a continuous spectrum from 275 to 390 nm, with a peak emission at 313 nm; B65% of that radiation is within the UVB wave range. The irradiance was 3.8 J/m 2 per second at a distance of 40 cm as measured by a UVR-305/365D digital radiometer (Tokyo Kogaku Kikai KK, Tokyo, Japan).…”
Section: Uvb Irradiation and Assessment Of Its Effects On Skinmentioning
confidence: 99%
“…8-oxo-7,8-dihydroguanine (8-oxoG) is a major oxidized base in DNA (12), and its accumulation is associated with various diseases, including cancer and neurodegeneration (13)(14)(15). In an earlier study, we demonstrated that 8-oxoG is increased in the retina of animal models of RP and the vitreous of RP patients (16).…”
Section: Introductionmentioning
confidence: 99%